ANALISIS NILAI KARAKTER DALAM TRADISI TEPUNG TAWAR PADA PERNIKAHAN MELAYU ROKAN HULU SEBAGAI BAHAN BELAJAR SISWA SDN 003 KEPENUHAN - Titin Lestari Solehat; Erlisnawati; Zetra Hainul Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the character values contained in the tepung tawar tradition at Malay weddings in Rokan Hulu, which can be used as teaching materials for students at SDN 003 Kepunahan. The type of research conducted is qualitative research with an ethnographic method. The variables studied include the tepung tawar tradition process and the character values present in Rokan Hulu Malay weddings. The results show that the tepung tawar tradition process in Rokan Hulu Malay weddings is led by traditional leaders and involves a series of activities, such as sprinkling tepung tawar water on the bride and groom, touching tepung tawar leaves from the head to the feet of the couple, scattering yellow rice on their heads, and concluding with a prayer. Additionally, the values contained in the tepung tawar tradition at Rokan Hulu Malay weddings include religious values, unity, mutual cooperation, fostering relationships, and social values.